2015
DOI: 10.3109/00207454.2015.1094473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive facilitative exercise with neuromuscular electrical stimulation, vibratory stimulation and repetitive transcranial magnetic stimulation of the hemiplegic hand in chronic stroke patients

Abstract: RFE with NMES, DAVS may be more effective than RFE with rTMS for the recovery of upper-limb function. Patients who received RFE with NMES, DAVS and pharmacological treatments showed significant functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Decrease in spasticity and increases in motor and cognitive functions also resulted with improvements in functional outcomes in our study. Etoh et al (2016) in another study, aimed to retrospectively compare the effects of repetitive facilitative exercise (RFE), neuromuscular electrical stimulation (NMES), direct application of vibratory stimulation (DAVS) and rTMS, and to determine the maximal effect of the combination of RFE with NMES, DAVS, rTMS, and pharmacological treatments in chronic stroke patients. Different from our study and other previously mentioned studies, rTMS was found to be less effective than NMES and DAVS in this study and a combination of RFE with NMES or DAVS was suggested instead of a combination with rTMS for the recovery of upper limb function.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in spasticity and increases in motor and cognitive functions also resulted with improvements in functional outcomes in our study. Etoh et al (2016) in another study, aimed to retrospectively compare the effects of repetitive facilitative exercise (RFE), neuromuscular electrical stimulation (NMES), direct application of vibratory stimulation (DAVS) and rTMS, and to determine the maximal effect of the combination of RFE with NMES, DAVS, rTMS, and pharmacological treatments in chronic stroke patients. Different from our study and other previously mentioned studies, rTMS was found to be less effective than NMES and DAVS in this study and a combination of RFE with NMES or DAVS was suggested instead of a combination with rTMS for the recovery of upper limb function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have studied the synergistic effects of different therapies on limb function recovery after stroke and found that they were more pronounced than single treatment [ 7 , 42 ]. So the next step, we will study the synergistic effects of FMS and some other therapies on GHS and upper limb function in hemiplegic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that RFE might promote functional recovery of hemiplegia and activities of daily living to a greater extent than conventional neurofacilitation therapy, using a randomized controlled design 2 , 3 , 4 , 5 , 19 , 20 ) . Especially, RFE with other interventions (i.e., neuromuscular electrical stimulation, direct application of vibratory stimulation repetitive transcranial magnetic stimulation, and pharmacological treatments) may be more effective than RFE only for the recovery of limb motor performance.…”
Section: Discussionmentioning
confidence: 99%